VEGETABLE STABILIZERS USED IN THE PRODUCTION OF FERMENTED MILK DRINKS AND YOGURTS - Smolnikova, Farida; Rebezov, Maksim; Shaydullin, Radik; Knysh, Irina; Yudina, Olga; Nikolaeva, Natalia; Sorokin, Aleksandr; Zubtsova, Yulia; Kozlov, Valeriy (International Journal of Psychosocial Rehabilitation, 2020)
The use of stabilisers in the production of fermented milk drinks is discussed in this article. It explains the key features of the stabilizers, the implementation process and their properties. Stabisol stabilisers characteristics are given. It is defined that stabilizers increase the value of food and promote the formation of a product consistency, and give a product antioxidant property.